Social, Economic Impact of HIV/AIDS on Handicraft Micro-Enterprises in Botswana - Mainah, J.; Mburu, Paul T. (Prabandhan: Indian Journal of Management, 2009)
One of the common Micro Enterprises (MEs) recognised in Botswana is the production and selling of handicrafts targeting tourism industry and in the process creating employment for Botswana. Tourism has been identified as an engine of economic growth and diversification in Botswana. However, challenges posed by Human Immune Virus and Acquired Immune Deficiency Syndrome (HIV/AIDS) have affected all sectors of the economy including the handicrafts industry. There is a need therefore to investigate the Social economic impacts of HIV/AIDS on handicraft micro enterprises in Botswana. Using a structured questionnaire, the study collected data from a randomly selected sample 302 handicraft dealers. Application of analysis of variance (ANOVA) was used to take into account the comparison of various responses. The study found out that the significant factors that affect the management of MEs included educational levels, income level, raw materials source, transport mode, sickness and nationality of handicraft dealers. The primary effect of HIV/AIDS included effects on productivity, time out of business, income levels, while secondary effects included qualities and quantities of raw materials/products including their transportation. The study recommends development of training packages to address handicraft sector on HIV/AIDS and on business management issues.